EDUCATION AND THE VALI-VAZAHA: BETWEEN TRADITION AND EDUCATIONAL PERSPECTIVES IN THE SOUTH-WEST REGION OF MADAGASCAR - Bien-Aimé, Whega Danitsaike; Bernard, Koto; Emynorane, Ralaivao Hanginiaina (Global Education Trends, 2025)
This study explores the phenomenon of vali-vazaha, marriage or concubinage with foreigners in the Southwest region of Madagascar, where tourism strongly influences local socio-cultural practices. While education is widely recognized as a fundamental right and a cornerstone of sustainable development, many families continue to prioritize early marriage, particularly with vazaha, as a faster route to economic and social mobility. Employing a qualitative field-based approach, data were collected through semi-structured interviews, questionnaires, and participant observation in three rural coastal communes: Itampolo, Belalanda (Mangily), and Befandefa (Andavadoaka). A purposive sample of 30 participants, including parents, young girls, teachers, and community leaders, provided diverse perspectives on the interplay between education, tradition, and marriage practices. The findings reveal a paradox: although education is acknowledged as valuable, its long-term benefits are often overshadowed by the immediate financial advantages of early marriage. Tourism and exposure to foreigners have reshaped local aspirations, reinforcing the perception of marriage with a vazaha as a shortcut to prestige and stability. Girls are the most affected, as they face school dropout, limited autonomy, and early social responsibilities. The study highlights how economic insecurity entrenched cultural norms, and weak institutional support collectively perpetuate this practice. By analyzing these dynamics through Bourdieu's theory of cultural capital, Berry's acculturation framework, and Durkheim's perspective on social norms, the study contributes a novel understanding of how globalization and local traditions intersect in shaping educational trajectories. It underscores the urgent need for context-sensitive policies that both strengthen educational opportunities for girls and address the socio-economic drivers of early marriage.